The Inventory of ferns (Pteridophyta) in East Citorek, Lebak, Banten - Nugraheni, Latif Sofiana; Survani, Rifki; Arindri, Dinda (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2024)
East Citorek Village in Lebak Regency is a village that has a beautiful, cool and lush environment, and there are a lot of springs. These environmental conditions support the growth of various types of ferns. The people of East Citorek Village are not aware of varied types of ferns in their area. With the development plan of East Citorek Village as one of tourist destinations that is in the process of building facilities and accessibility, it is feared that it bears the potential to reduce and annihilate fern vegetation. The purpose of this study was to identify the types of fern (Pteridophyta) and determine the abiotic factors of ferns (Pteridophyta) at East Citorek Village, Lebak Regency. This research uses incorporates a qualitative approach using the cruise method, particularly by observing directly and exploring each place that is considered representative of the fern vegetation that becomes the concern of the study. Each type of fern plant was sampled to be identified and collected as a dry herbarium. The results of the study found that there were 19 species, 12 families, and 7 orders of fern in the area. The most common type of fern plant found comes from the Polypodiaceae family, while the type of fern that dominates the study site is the species of Dicranopteris linearis. The results of measuring environmental abiotic factors at East Citorek Village in Lebak Regency show that the results are still feasible for the survival of ferns within the average temperature measurement of 28◦C, air humidity of 76.3%, and soil pH of6.Keywords: Identification, Fern, Pteridophyta, Herbarium